Comparison of perioperative outcomes in frail patients following multilevel lumbar fusion surgery with and without the implementation of the enhanced recovery after surgery protocol - Cui, Peng; Wang, Shuaikang; Wang, Peng; Yang, Lijuan; Kong, Chao; Lu, Shibao (Frontiers in Surgery, 2022)
Background Enhanced recovery after surgery (ERAS) is an evidence-based multimodal perioperative management designed to reduce the length of stay (LOS) and complications. The purpose of the present study is to evaluate the recovery of physiological function, LOS, complications, pain score, and clinical efficacy in frail elderly patients undergoing multisegment fusion surgery after the implementation of the ERAS protocol. Methods Frail patients older than 75 years undergoing multilevel lumbar fusion surgery for degenerative discogenic conditions, lumbar spinal stenosis, and lumbar spondylolisthesis from January 2017 to December 2018 (non-ERAS frail group) and from January 2020 to December 2021 (ERAS frail group) were enrolled in the present study. Propensity score matching for age, sex, body mass index, and smoking status was performed to keep comparable characteristics between the two groups. Further recovery of physiological function, LOS, complications, pain score, and clinical efficacy were compared between the groups. Results There were 64 pairs of well-balanced patients, and the clinical baseline data were comparable between the two groups. There was significant improvement in terms of recovery of physiological function (10.65 ± 3.51 days vs. 8.31 ± 3.98 days, p = 0.011) and LOS (12.18 ± 4.69 days vs. 10.44 ± 4.60 days, p = 0.035), while no statistical discrepancy was observed with regard to complications between the groups, which indicated favorable outcomes after the implementation of the ERAS protocol. Further analysis indicated that more patients were meeting a minimally clinical important difference for the visual analog score for the legs and the Oswestry Disability Index in the ERAS frail group. With regard to postoperative pain, the score was higher in the ERAS frail group than in the non-ERAS frail group on postoperative day (POD) 1 (4.88 ± 1.90 in the ERAS frail group vs. 4.27 ± 1.42 in the non-ERAS frail group, p = 0.042), while there was no significant discrepancy on POD 2 (3.77 ± 0.88 in the ERAS frail group vs. 3.64 ± 1.07 in the non-ERAS frail group, p = 0.470) and POD 3 (3.83 ± 1.89 in the ERAS frail group vs. 3.47 ± 1.75 in the non-ERAS frail group, p = 0.266). Conclusions In this retrospective cohort study, we found a significant improvement in terms of LOS, recovery of physiological function, and clinical efficacy after the implementation of the ERAS protocol in elderly and frail patients undergoing multilevel lumbar fusion surgery, while there was no significant discrepancy with regard to complications, 90-day readmission, and postoperative pain.